1988
DOI: 10.1126/science.3291117
|View full text |Cite
|
Sign up to set email alerts
|

Yeast KEX2 Endopeptidase Correctly Cleaves a Neuroendocrine Prohormone in Mammalian Cells

Abstract: Mammalian cell lines (BSC-40, NG108-15, and GH4C1) that cannot process the murine neuroendocrine peptide precursor prepro-opiomelanocortin (mPOMC) when its synthesis is directed by a vaccinia virus vector were coinfected with a second recombinant vaccinia virus carrying the yeast KEX2 gene, which encodes an endopeptidase that cleaves at pairs of basic amino acid residues. mPOMC was cleaved intracellularly to a set of product peptides normally found in vivo, including mature gamma-lipotropin and beta-endorphin1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
90
0

Year Published

1989
1989
2001
2001

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 176 publications
(92 citation statements)
references
References 47 publications
2
90
0
Order By: Relevance
“…The release of the protein was not due to cell lysis, because as shown by microscopic observation, the cells at the time of harvesting had a healthy morphology and had not lysed. Transient expression of the KEX2 gene in mammalian cells using a vaccinia virus expression system also resulted in secretion of 25-50% of the enzyme (Thomas et al, 1988) which is in marked contrast to full retention of Kex2p in yeast cells or stable mammalian cell lines expressing this protease (Germain et al, 1990). These observations may indicate that the use of viral expression systems perturbes the transport and/or the intracellular localization of Kex2p.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…The release of the protein was not due to cell lysis, because as shown by microscopic observation, the cells at the time of harvesting had a healthy morphology and had not lysed. Transient expression of the KEX2 gene in mammalian cells using a vaccinia virus expression system also resulted in secretion of 25-50% of the enzyme (Thomas et al, 1988) which is in marked contrast to full retention of Kex2p in yeast cells or stable mammalian cell lines expressing this protease (Germain et al, 1990). These observations may indicate that the use of viral expression systems perturbes the transport and/or the intracellular localization of Kex2p.…”
Section: Discussionmentioning
confidence: 59%
“…Kex2p was shown to be a Ca2+-dependent endoprotease that cleaved at the carboxy side of pairs of basic amino acids such as Lys -Arg or ArgArg (Fuller et al, 1989). Co-transfection of the yeast KEX2 gene and of proopiomelanocortin (POMC) cDNA into mammalian cells that cannot normally process the POMC precursor showed that the yeast enzyme could process the POMC precursor in a cellular environment (Thomas et al, 1988;Zollinger et al, 1990;Germain et al, 1990). These recent reports have engendered an interest in further biochemical characterization of the Kex2p endoprotease.…”
mentioning
confidence: 99%
“…In addition to these natural functions, the Kex2 protease can mediate the processing of proinsulin and proalbumin expressed in yeast (21,22) and can properly cleave the propeptide of proalbumin in vitro (23). Finally, Kex2 can function in transfected murine cells to process proopiomelanocortin prohormone to product peptides normally found in vivo (11).…”
mentioning
confidence: 99%
“…3 and 4). These cleavages remove propeptides that function in a variety of essential roles in the maturation of the precursor proteins including (i) correct folding and disulfide bond formation (5,6), (ii) y-carboxylation of glutamic acid residues (7,8), (iii) directing intracellular targeting (9), and (iv) regulating the coordinate synthesis of multiple mature peptides from a single precursor polypeptide, typified by proopiomelanocortin (10,11). In addition to these natural cellular products, several viral polyproteins require cleavage at paired basic amino acid residues.…”
mentioning
confidence: 99%
“…Striking examples are the yeast KEX2-encoded proteinase yscF (Julius et al, 1984; Achstetter and Wolf, 1985b), which has been shown to be the prototype of a eucaryotic hormone-processing enzyme (Barr, 1991; Thomas et al, 1988) or proteinase yscE, the yeast proteasome involved in stress and ubiquitin-signalled proteolysis in the cytoplasm of cells (Heinemeyer et al, 1991; Hilt and Wolf, 1992; Richter-Ruoff et al, 1992), subunits of which share up to 60% identity with their mammalian counterparts (Heinemeyer et al, 1993).…”
mentioning
confidence: 99%